A simple arthroscopic technique for treatment of displaced “hinged” type of posterior cruciate ligament avulsion fractures - Zheshu Xu; Yunlong Dong; Yu-e Feng; Peng Xie; Juyuan Gu; Kai Kang; Shijun Gao; Xiaozuo Zheng (BMC Musculoskeletal Disorders, 2022)
Abstract Background The surgical technique for treatment of tibial avulsion fractures of the posterior cruciate ligament (PCL) remains challenging due to the deep-located lesion and the complexity of the anatomy. The purpose of this study was to report preliminary results of an arthroscopic technique in patients with the “hinged” type PCL tibial avulsion fractures. Methods Twenty-eight patients with the displaced “hinged” fractures with elevation of the posterior aspect of the bony fragment were arthroscopically treated. The bony fragment was reducted and fixed with the sutures passing through only one single tibial tunnel. The clinical outcomes were assessed by Lysholm score, Tegner activity score, and the side-to-side differences of KT-1000 measurement. The reduction and union of the fracture were assessed by radiography of the knee. Results Patients were followed up for a mean of 19 (12 to 24) months. There were no surgery-related complications, and all patients regained normal range of motion of the knees at the last follow-up. The Lysholm score significantly increased from preoperative 14.78 ± 8.23 to postoperative 96.96 ± 3.62 (P = 0.000). The Tegner score was 6.78 ± 1.35 pre-injury and 6.48 ± 1.20 at the last follow-up with no statistical difference (P = 0.688). The KT-1000 side-to-side differences significantly decreased from 8.26(SD 1.86; 6 to 12) pre-operatively to 0.91 (SD 0.85; 0 to 3) (P = 0.000). X-rays showed that satisfactory reduction and solid union was achieved in all patients. Conclusion The arthroscopic suture fixation through single-tibial tunnel technique yielded good clinical and radiographic outcome for treatment of displaced “hinged” type of PCL avulsion fractures.